2022
DOI: 10.3389/fevo.2022.913279
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Fish Community Composition Accessed by Electrofishing, Gill Netting, Seining, Trawling, and Water eDNA Metabarcoding in Temperate Reservoirs

Abstract: It is difficult to understand the composition and diversity of biological communities in complex and heterogeneous environments using traditional sampling methods. Recently, developments in environmental DNA metabarcoding have emerged as a powerful, non-invasive method for comprehensive community characterization and biodiversity monitoring in different types of aquatic ecosystems. In this study, water eDNA targeting fish (wf-eDNA) and four traditional fish sampling methods (electrofishing, gill netting, seini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Gillnets can be used to compare the species composition and relative density of fish in different water bodies, but in view of the restricted migration times of fish, which influence the probability of being caught (Prchalová et al, 2010), gillnets are not a suitable method for investigating diurnal patterns in fish distribution. As a combination of several techniques is often required to obtain a true picture of the fish community (Golpour et al, 2022; Kubečka et al, 2009), the intercalibration of different sampling techniques should not be disregarded in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Gillnets can be used to compare the species composition and relative density of fish in different water bodies, but in view of the restricted migration times of fish, which influence the probability of being caught (Prchalová et al, 2010), gillnets are not a suitable method for investigating diurnal patterns in fish distribution. As a combination of several techniques is often required to obtain a true picture of the fish community (Golpour et al, 2022; Kubečka et al, 2009), the intercalibration of different sampling techniques should not be disregarded in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is such a way to compare the effectiveness of eDNA to the conventional practice of identifying fish. Some studies have also compared the effectiveness of eDNA in identifying fish diversity against gillnetting (Golpour et al 2022;Li et al 2023). The gillnet was deployed at exactly the same point where the water was taken.…”
Section: Conventional Methods Of Catching Fishmentioning
confidence: 99%
“…It is important to note that traditional methods may still have advantages in certain occasions which could basically complement the weakness of eDNA. For instance, a study comparing eDNA and traditional sampling methods observed that some species such as Pseudorasbora parva, Carassius carassius and Lota lota were only detected using traditional sampling gears, while eDNA unsuccessfully detected the presence of these fishes (Golpour et al 2022). Another study reported that some fish species have been detected using gill nets but not with eDNA, including rare and invasive fishes such as non-native species like…”
Section: Comparison Between Edna Metabarcoding and Conventional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of environmental DNA (eDNA) methods and the related bioinformatics analyses has provided researchers with the ability to explore the biodiversity of aquatic communities via eDNA metabarcoding or to detect individual species via quantitative PCR (qPCR) (Cantera et al., 2022; Lacoursière‐Roussel et al., 2016; Laporte et al., 2021; Pilliod et al., 2013; Yang et al., 2021). These approaches, especially eDNA metabarcoding—the sequencing and characterization of all DNA of a given taxonomic group in an environmental sample—are now routinely applied in biodiversity and ecological studies across all types of ecosystems (Boivin‐Delisle et al., 2021; Closek et al., 2019; Czeglédi et al., 2021; Evans et al., 2016; Gamage et al., 2020; García Machado et al., 2022; Golpour et al., 2022; Harper et al., 2019; Hashemzadeh Segherloo, Tabatabaei, Abdolahi‐Mousavi, et al., 2022; McColl‐Gausden et al., 2021; Mena et al., 2021; Newton et al., 2023; Ritter et al., 2022; Roger et al., 2022; Sales et al., 2020; Yonezawa et al., 2020; Zhang et al., 2023). Among its advantages, eDNA is very sensitive, nondestructive, and noninvasive compared to conventional methods.…”
Section: Introductionmentioning
confidence: 99%